Detection of blaNDM-1 gene among the carbapenem resistant Escherichia coli and Klebsiella pneumoniae isolates from a children’s hospital in Nepal - Binod, G.C.; Nim Raj Sapkota; Binod Rayamajhee; Jayram Lamichhane; Pramod Poudel; Sunil Lekhak; Shovana Thapa; Santosh Khanal (Novel Research in Microbiology Journal)
This study was undertaken to detect the presence of blaNDM-1 gene among the carbapenem resistant Escherichia coli and Klebsiella pneumoniae isolates, confirmed through using Modified Hodge Test (MHT). During the six months of this study (November, 2016 – April, 2017), a total of 1503 clinical samples including urine, blood, wound swabs and Cerebrospinal fluid (CSF) were collected and processed at Microbiology Laboratory, International Friendship Children’s Hospital, Kathmandu, Nepal. Among the E. coli and K. pneumoniae isolates, 14.1%, 17.1% were resistant to meropenem, whereas 11.28%, 17.1% were resistant to imipenem, respectively. From the pool of 94 E. coli and 35 K. pneumoniae isolates, 34 E. coli and 18 K. pneumoniae were screened as possible carbapenemase producers. For screening of carbapenemase enzyme production among these isolates, resistances to third generation cephalosporins and carbapenems were taken into consideration. Two isolates of E. coli and 3 isolates of K. pneumoniae were confirmed as carbapenemase producers by MHT. Furthermore, Polymerase chain reaction (PCR) was carried out among the MHT positive bacteria for detection of blaNDM-1 gene. Genetic analysis of MHT positive isolates showed that 1\2 E. coli and 2\3 K. pneumoniae isolates were New Delhi metallo-β-lactamase producers (NDM-1). Results of this study demonstrated the presence of blaNDM-1 gene among the carbapenemase producing E. coli and K. pneumoniae isolates, and were recorded to be 50% and 66.6%, respectively.